Processing and characterization of low-cost electrospun carbon fibers from organosolv lignin/polyacrylonitrile blends - Ding, Rui; Wu, Hongchao; Thunga, Mahendra; Bowler, Nicola; Kessler, Michael R. (Carbon (New York), 2016)
The esterification of lignin with butyric anhydride decreases both the viscosity of lignin/PAN blend spinning solutions and their glass-transition temperature compared to unmodified lignin/PAN blends. The effect of blending PAN with lignin before or after butyration on the electrospinnability, miscibility and thermal stability of precursor blend fibers was investigated by morphological, rheological, and thermal analysis. The micromorphology, carbon structure, and mechanical properties of resultant carbonized fibers (CFs) were further evaluated. This study reveals a new approach to controlling inter-fiber bonding of lignin-based carbon nanofiber mats by manipulating the molecular structure of lignin while following a standard procedure of thermo-stabilization and carbonization treatment. Characterization results indicate that inter-fiber bonding in electrospun CF mats, induced by the high thermal mobility of butyrated lignin, favorably affected their mechanical properties.